Human Defensins: A Novel Approach in the Fight against Skin Colonizing Staphylococcus aureus - Scudiero, Olga (Antibiotics (Basel), 2020)
Staphylococcus aureus is a microorganism capable of causing numerous diseases of the human skin. The incidence of S. aureus skin infections reflects the conflict between the host skin′s immune defenses and the S. aureus’ virulence elements. Antimicrobial peptides (AMPs) are small protein molecules involved in numerous biological activities, playing a very important role in the innate immunity. They constitute the defense of the host′s skin, which prevents harmful microorganisms from entering the epithelial barrier, including S. aureus. However, S. aureus uses ambiguous mechanisms against host defenses by promoting colonization and skin infections. Our review aims to provide a reference collection on host-pathogen interactions in skin disorders, including S. aureus infections and its resistance to methicillin (MRSA). In addition to these, we discuss the involvement of defensins and other innate immunity mediators (i.e., toll receptors, interleukin-1, and interleukin-17), involved in the defense of the host against the skin disorders caused by S. aureus, and then focus on the evasion mechanisms developed by the pathogenic microorganism under analysis. This review provides the “state of the art” on molecular mechanisms underlying S. aureus skin infection and the pharmacological potential of AMPs as a new therapeutic strategy, in order to define alternative directions in the fight against cutaneous disease.